Cavitation erosion-corrosion properties of as-cast TC4 and LPBF TC4 in 0.6 mol/L NaCl solution: A comparison investigation - Yang, Zhou; Li, Liang; Qiao, Yanxin; Li, Chengtao; Zhang, Lianmin; Cui, Jie; Ren, Dechun; Ji, Haibin; Zheng, Yugui (Ultrasonics sonochemistry, 2024)
•Synergistic effect of CE-corrosion on as-cast TC4 and SLM TC4 was quantitatively evaluated.•Electrochemical mixed potential theory was under discussion in the CE process of as-cast TC4 and SLM TC4.•SLM TC4 has superior CE resistance compared with as-cast TC4.•Mechanism of CE damage for as-cast TC4 and SLM TC4 in 3.5 wt% NaCl solution was elucidated. In this work study, a comparative analysis was undertaken to investigate investigation into the cavitation erosion (CE) and corrosion behavior of laser powder bed fusion (LPBF) TC4 and as-cast TC4 in 0.6 mol/L NaCl solution. Relevant results indicated that LPBF TC4 revealed a rectangular checkerboard-like pattern with a more refined grain size compared to as-cast TC4. Meanwhile, LPBF TC4 surpassed its as-cast counterpart in CE resistance, demonstrating approximately 2.25 times lower cumulative mass loss after 8 h CE. The corrosion potential under alternating CE and quiescence conditions demonstrated that both LPBF TC4 and as-cast TC4 underwent a rapid potential decrease at the initial stages of CE, while a consistent negative shift in corrosion potential was observed with the continuously increasing CE time, indicative of a gradual decline in repassivation ability. The initial surge in corrosion potential during the early CE stages was primarily attributed to accelerated oxygen transfer. As CE progressed, the significant reduction in corrosion potential for both LPBF TC4 and as-cast TC4 was attributed to the breakdown of the passive film. The refined and uniform microstructure in LPBF TC4 effectively suppresses both crack formation and propagation, underscoring the potential of LPBF technology in enhancing the CE resistance of titanium alloys. This work can provide important insights into developing high-quality, reliable, and sustainable CE-resistant materials via LPBF technology.